Nonlinear systems and their remarkable mathematical structures - Euler, Norbert (Boca Raton, Florida : CRC Press, 2019)
"The book aims to describe some recent progress in nonlinear differential equations and nonlinear dynamical systems (both continuous and discrete)"--
Systems of nonlinearly-coupled dierential equations solvable by algebraic operations / F. Calogero -- Integrable nonlinear PDEs on the half-line / A S Fokas and B Pelloni -- Detecting discrete integrability: the singularity approach / B. Grammaticos, A Ramani, R Willox and T Mase -- Elementary introduction to discrete soliton equations / J Hietarinta -- New results on integrability of the Kahan-Hirota-Kimura discretizations / Yu B Suris and M Petrera -- Dynamical systems satisfied by special polynomials and related isospectral matrices defined in terms of their zeros / O Bihun -- Singularity methods for meromorphic solutions of differential equations / R Conte, T W Ng and C Wu -- Pfeiffer-Sato solutions of Buhl's problem and a Lagrange-D'Alembert principle for Heavenly equations / O E Hentosh, Ya A Prykarpatsky, D Blackmore and A Prykarpatski -- Superposition formulae for nonlinear integrable equations in bilinear form / X B Hu -- Matrix solutions for equations of the AKNS system / C Schiebold -- Algebraic traveling waves for the generalized KdV-Burgers equation and the Kuramoto-Sivashinsky equation / C Valls -- Nonlocal invariance of the multipotentialisations of the Kupershmidt equation and its higher-order hierarchies / M Euler and N Euler -- Geometry of normal forms for dynamical systems / G Gaeta -- Symmetries of It^o stochastic differential equations and their applications / R Kozlov -- Statistical symmetries of turbulence / M Oberlack, M Waclawczyk and V Grebenev -- Integral transforms and ordinary differential equations of infinte order / A Chavez, H Prado and E G Reyes -- The role of nonlinearity in geostrophic ocean flows on a sphere / A Constantin and R S Johnson -- Review of results on a system of type many predators-one prey / A V Osipov and G Soderbacka -- Ermakov-type systems in nonlinear physics and continuum mechanics / C Rogers and W K Schief.
OCLC-licensed vendor bibliographic record.
Keywords: Nonlinear theories; Differential equations, Nonlinear; Nonlinear systems; MATHEMATICS / Calculus; MATHEMATICS / Mathematical Analysis; MATHEMATICS / Applied; MATHEMATICS / Arithmetic; MATHEMATICS / Differential Equations